Centralized versus decentralized pricing controls for dynamic matching platforms - ALI, Aouad (Institutional Knowledge at Singapore Management University, 2023)
Online service platforms have transformed how customers and suppliers connect in real-time, using centralized dispatch and pricing systems. However, by acting as "central planners", platforms risk undermining the workers' flexibility endorsed by the gig economy. Hence, there has been significant scrutiny on the classification of gig workers as independent contractors and their freedom in decisions that directly influence their earnings, such as prices. To alleviate such concerns, several platforms in the ride-hailing industry have adopted or tested decentralized pricing schemes, where workers set prices flexibly. However, this approach presents a complex trade-off. On the one hand, platforms' pricing systems enable an efficient matching process by balancing demand and supply. Individual suppliers' pricing decisions may overlook market-wide effects on supply-demand equilibrium. On the other hand, suppliers possess private information about their preferences and costs that platforms cannot easily infer and use for price discrimination. Decentralized pricing can accommodate supplier-side heterogeneity, potentially increasing workers' participation in the market.